Warunki powstawania odnowień naturalnych sosny zwyczajnej (Pinus sylvestris L.) na terenie Nadleśnictwa Tuszyma - Dobrowolska, Dorota (Leśne Prace Badawcze, 2010)
The aim of the study was to assess how well natural regeneration of Scot pine could establish and grow in the Tuszyma Forest District in southern Poland. Specifically, the relative growth of pine regeneration in forest plots at two site types was compared as a proxy for their health and performance. Two approaches were used: firstly, the general state of natural regeneration in the Tuszyma Forest District was assessed. Secondly, a census was made of pine regeneration in circular plots (area 10 m 2 ) over a 20 × 20 m area in a network covering 6 study stands. The following measurements were taken from each study plot: height, height increment in 2006 and the vitality of pine regeneration. The results confirmed that pine regenerates naturally at the 6 site types monitored in Tuszyma Forest District. Natural regeneration of Scots pine was especially strong on fresh mixed coniferous site type (BMśw). Successful regeneration requires that the soil is prepared before seed dispersal in the autumn: this can be best achieved using a soil miller. The area of Scots pine natural regeneration in the Tuszyma Forest District was 213,4 ha. The method most frequently used to initiate pine regeneration was clear cut of a strip of width 30–60 m. Although other methods were also used, especially a shelterwood group system, site type did not influence the extent of pine regeneration. The amount of pine regeneration was not dependent on mast year. Site conditions influenced the height of pine regeneration and the height increment. The average height and height increment were significantly higher on the fresh mixed deciduous site type (LMśw) than on the fresh mixed coniferous site type (BMśw). The vitality of pine was very good on both sites and did not depend on the site type. The level of damage was low irrespective of site.